2019
DOI: 10.2147/ijn.s193679
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nematicidal activity of silver nanoparticles from the fungus <em>Duddingtonia flagrans</em></p>

Abstract: Background: Helminth parasites cause morbidity and mortality in both humans and animals. Most anthelmintic drugs used in the treatment of parasitic nematode infections act on target proteins or regulate the electrical activity of neurons and muscles. In this way, it can lead to paralysis, starvation, immune attack, and expulsion of the worm. However, current anthelmintics have some limitations that include a limited spectrum of activity across species and the threat of drug resistance, which highlights the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 26 publications
2
23
0
1
Order By: Relevance
“…Moreover, AgNPs synthesized by Cryphonectria sp. showed antibacterial activity against various human pathogenic bacteria, including S. aureus , Klebsiella pneumoniae , E. coli , Salmonella typhi and Candida albicans [ 9 , 30 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Nanomaterials As New Potential Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AgNPs synthesized by Cryphonectria sp. showed antibacterial activity against various human pathogenic bacteria, including S. aureus , Klebsiella pneumoniae , E. coli , Salmonella typhi and Candida albicans [ 9 , 30 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Nanomaterials As New Potential Antibioticsmentioning
confidence: 99%
“…Biologically synthesized AgNP stabilized additionally with sodium dodecyl sulfate and analysis of MIC tests showed increased antifungal activity compared to fluconazole often used in hospitals in relation to clinical isolates and ATCC strains: Trichophyton mentagrophytes , Phoma glomerata , Phoma herbarum , Fusarium semitectum , Trichoderma sp., Candida albicans , Candida glabrata , Aspergillus niger and Issatchenkia orientalis [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 73 , 74 , 75 , 76 ]. Biologically synthesized AgNPs showed antifungal activity against phytopathogens such as Alternaria alternata , Sclerotinia sclerotiorum , Macrophomina phaseolina , Rhizoctonia solani , Botrytis cinerea and Curvularia lunata Fusarium oxysporum [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 73 , 74 , 75 , 76 ].…”
Section: Conventional Silver Preparations Used In Medicinementioning
confidence: 99%
“…[16,[20][21][22]. Synthesis of AgNPs via fungi gain more attention because they produce large amount of biomass in a short period of time under lab conditions and produce large amount of extracellular protein that help in synthesis of nanoparticles [23,24]. Dhanaraj et al [17] observed the AgNPs synthesis potential of fungi Aspergillus niger and observed significant anti-bacterial properties of AgNPs against Staphylococcus aureus, Klebsiella pneumonia, Escherichia coli, and Salmonella typhi.…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis represents a low-cost, environmentally friendly way of producing AgNPs without using high temperatures and pressures [46]. Typically, the plant [46][47][48][49][50], fungus [51][52][53] or bacteria extract is mixed with silver ions containing salt (silver nitrate is mainly used [46][47][48][49][50][51][52][53]) and bioactive molecules of extracts reduce silver ions to elementary silver. A huge advantage of using plant extracts is the fact that many plants contain health-beneficial compounds, also known from their use in conventional medicine (for example, paclitaxel, vincristine or artemisinin) [54].…”
Section: Synthesis Of Agnpsmentioning
confidence: 99%